The Urgency of Mutual Legal Assitance in Criminal Matters (MLA) in Action Against of Corruption - Miko Aditiya Suharto; Maria Novita Apriyani; Waluyo (Future Science, 2022)
The handling of transnational crimes, namely corruption, requires the support of cooperation with other countries, both informally and formally between countries. The regulation of asset return is stated in the Opening of the United Nations Convention Against Corruption in 2003. Assets resulting from corruption crimes by perpetrators are mostly taken abroad and recovery in Indonesia faces challenges and obstacles. One of the factors that become an obstacle in the process of returning assets resulting from corruption transnationally is related to the return of assets when the requesting country and the requested country do not have bilateral agreements such as extradition and Mutual Legal Assistance. The problems that will be raised in this study are (1) how is the implementation of requests for mutual legal assistance in criminal matters (MLA) for perpetrators of corruption? (2) what are the obstacles and challenges in the process of mutual legal assistance in criminal matters (MLA) in prosecuting perpetrators of criminal acts of corruption in Indonesia? The writing of this legal article belongs to the category of socio-legal research or empirical law. The research approach applied in writing this scientific article uses a statutory approach, a conceptual approach, and a case approach. The data collection technique used in this paper is a field study taking data through interviews with the Directorate of Central Authority and International Law, Ministry of Law and Human Rights. The results obtained in this study are the renewal of the extradition law of the State of Indonesia is very important to do considering not only repatriating convicts but also adding regulations for the return of assets resulting from corruption abroad through Mutual Legal Assistance, regulation of assets of wealth convicts of corruption as a preventive measure. and repressive measures to be frozen, confiscated, and repatriated to Indonesia from abroad.